Construction of High-Density Genetic Map and Identification of a Bruchid Resistance Locus in Mung Bean (Vigna radiata L.) - Chen, Tianxiao; Hu, Liangliang; Wang, Suhua; Wang, Lixia; Cheng, Xuzhen; Chen, Honglin (Frontiers in Genetics, 2022)
Mung bean (Vigna radiata. L.) is an economically important grain legume cultivated in Asian countries. High-density genetic linkage is a valuable and eﬀective tool for mapping quantitative trait loci (QTL). In the present study, a high-resolution genetic map containing 4,180 single-nucleotide polymorphisms (SNPs) assigned to 11 linkage groups (LGs) and spanning 1,751.39 cM in length, was constructed for mung bean, and the average distance between the adjacent markers was 0.42 cM. Bruchids (Callosobruchus spp.) cause significant damage to and loss of legume seeds. A locus for bruchid resistance was detected. The gene Vradi05g03810, encoding a probable resistance-specific protein, was most likely a key candidate gene in mung bean. A 69-bp sequence deletion was identified in the coding region by comparing the cDNA sequences of bruchid-resistant and bruchid-susceptible lines, and the expression level of the gene was significantly higher in the bruchid-resistant lines than that in the bruchid-susceptible lines. This SNP-based high-density linkage map is one of the first to be constructed across the mung bean genome. This map will not only facilitate the genetic mapping of genes or complex loci that control important agronomic traits but also offer a tool for promoting future genetics and comparative genomic studies in Vigna.